A escolarização em Toledo: uma luz na escuridão da mata - Fundação Educacional de Toledo/PR - Lindner, Sandra Inês (2019)
This research aimed to discuss about the Fundação Educacional de Toledo – FUNET (Educational Foundation of Toledo), in the process of schooling of the municipality. We started from the Rio Branco School during the recolonization, post-dismemberment of Foz do Iguaçu city, through State Law no.790, dated 11/14/1951, sanctioned by the governor of the time, Bento Munhoz da Rocha Neto and executed on December 12th, in 1952. This work also analyzes the colonization of the Western Paraná state and the history of the city of Toledo, approaching the process of constitution of Funet in the context as one of first schools in Toledo. The reconstitution of education allowed organizing the set of sources on the history of the municipality, through documentary and iconographic sources. It made possible to understand not only local development, but also the educational process in Paraná and Brazil. In the analysis we take into account the historical, political, economic and social aspects emerging in the Western region of Paraná. School institutions had their roles drawn from their origins, characterization, and the context surrounding them, in which political, economic, and religious forces acted in the direction of educational modernization. FUNET is examined from its historical in 1974, as well as the participation of the Special Multinational Project and the Ministry of Education and Culture (MEC/OAS) in the educational process and teacher training in the city of Toledo. The conception of education expressed in this educational institution corresponded to the nationalist and developmentalist principles of the country, which spread the expansion of schooling.